Cation and spin ordering in the n=1 Ruddlesden-Popper phase La2Sr2LiRuO8 - Rodgers, J; Battle, P; Dupre, N; Grey, C; Sloan, J (2004)
The synthesis and characterization of a polycrystalline sample of the n = 1 Ruddlesden-Popper phase La2Sr2LiRuO8 are reported. X-ray and neutron diffraction show that the six-coordinate sites are occupied by 1:1 ordered xy layers of Li:Ru, and the nine-coordinate sites are occupied by 1:1 ordered layers of La:Sr; a low concentration (7.4%, 9.8% respectively) of anti-site defects was detected on each sublattice. These layers stack in an ordered sequence along z, resulting in an orthorhombic unit cell with a 5.46001(1), b = 5.45803(1), and c = 25.5410(2) Å (space group Imm2) at 290 K. The structure is confirmed by high-resolution transmission electron microscopy, although the presence of stacking faults is revealed. 7Li MAS NMR spectra are consistent with the diffraction data and show that the anti-site defects are not randomly distributed but occur in domains. The sample undergoes a transition to an antiferromagnetic phase at 85 K, with an ordered magnetic moment of 1.58(7) μB per Ru5+ aligned along [001]. The spins associated with the anti-site Ru cations freeze as a spin glass.